Impact of Methyl Parathion on Proteins and Esterases Patterns in Brain Tissue of Fresh Water Cat Fish Heteropneustes fossilis (Bloch) through Polyacrylamide Gel Electrophoresis - Rao, T. Bheem (Contemporary Research and Perspectives in Biological Science Vol. 2, 2024)
The present investigation aimed to assess the impact of Methyl Parathion, an organophosphate compound, on the protein and esterase isozyme banding patterns within the brain tissue of the freshwater catfish Heteropneustes fossilis (Bloch) over various time intervals (24, 48, 72, and 96 hours), in comparison to a control group. The analysis of protein banding patterns was conducted utilizing a standard marker, and Rm values were calculated as part of the study. The results indicated that exposure to methyl parathion induced significant alterations in the protein patterns across various tissues, including the liver, muscle, gut, and brain of Heteropneustes fossilis, leading to similarities in protein bands with minor differences. All three esterase bands were identified in the brain tissue. In liver tissue, Est-1 was found to be the most prominent at 24 hours, while Est-2 and Est-4 were most intense at 72 hours. Additionally, Est-2 and Est-3 exhibited weak staining in brain tissue, with Est-3 also showing weak staining in liver tissue and Est-4 in gut tissues. The results further illustrated that exposure to methyl parathion resulted in notable changes in the esterase patterns of various tissues, including the brain tissue of H. fossilis, which displayed similarities in protein bands with slight variations.